Roles of ADAM12 in triple-negative breast cancer: regulation of cancer stem cells - Qi, Yue (Kansas State University, 2016)
ADAM12 (A Disintegrin and Metalloprotease 12) is a cell surface protease, which is deregulated in many human diseases. High expression of ADAM12 in triple-negative breast cancers (lacking estrogen receptor, progesterone receptor, and HER2 expression) is associated with poor patient prognosis. My dissertation focused on the understanding of the biological functions of ADAM12 in triple-negative breast cancers. I found that ADAM12 is significantly upregulated in the claudin-low molecular subtype of breast cancer. Claudin-low tumors are typically triple-negative and are enriched in cancer stem cells. Here, I demonstrated that the loss of ADAM12 expression not only decreased the number of cancer stem-like cells in vitro but also significantly compromised the tumor-initiating capabilities of breast cancer cells in vivo. This is the first evidence showing that ADAM12 might regulate the cancer stem cell-like phenotype in triple-negative breast cancers. I also discovered a novel mechanism of ADAM12-regulated signaling by transforming growth factor β (TGFβ) through modulation of TGFBR1 mRNA expression in breast cancer cells. Lastly, I characterized the effects of six different somatic mutations in the ADAM12 gene found in human breast cancers on the intracellular trafficking, post-translational processing, and function of ADAM12 protein. Collectively, the findings of this study support the notion that ADAM12 with catalytically active metalloprotease domain is required for the progression of triple-negative breast cancers.
Keywords: Breast cancer; Cell signaling; Protein chemistry; Stem cells; Genetic mutations; Membrane receptors